A Risk-Return Measure of Hedging Effectiveness - Howard, Charles T.; D'Antonio, Louis J. (Journal of Financial and Quantitative Analysis, 1984)
With the formation of a formal market for the trading of financial futures in October 1975, a renewed interest in the futures contract as an investment vehicle has emerged. The traditional approach was to view investing in futures as a way of off setting potential price risk associated with a given spot position. While these descriptive scenarios (see [3], [6], [10], [12], [13], [14], and [19]) adequately illustrate the traditional hedging strategy, their simplifying assumptions introduce a lack of realism into the investment process. The implication drawn from many of these articles is that, if one is interested in risk reduction, one should simply take the opposite position in the appropriate number of futures contracts to totally offset one's existing spot position.